Pain Candidate Genes 5-HTTLPR and COMT Affect Anxiety and Mood in Japanese Ballet Dancers: A Cross-Sectional and Longitudinal Study - Kanaka Yatabe; Kohei Ashikaga; Ryota Muroi; Shu Somemura; Masahiro Takemoto; Kazuo Yudoh; Hisao Miyano; Hiroto Fujiya (Sports)
The balance of mental, physical, and technical aspects is essential in improving ballet performance. Ballet dancers’ emotional and behavioral characteristics vary, even under identical stress conditions. This study aimed to investigate the association between the pain candidate genes 5-HTTLPR and COMT and anxiety in Japanese ballet dancers. Participants were 18 youth elite ballet students with professional aspirations (Y-Elite) and 16 dancers in a professional ballet company (Pro). We administered psychological questionnaires, the State-Trait Anxiety Inventory (STAI) and Brunel Mood Scale (BRUMS), to participants under the following four different stress conditions: standard practice day, cast decision day, rehearsal day, and one week before competition day. In addition, the genotypes of 5-HTTLPR and COMT Val158Met were examined. The distribution of 5-HTTLPR was not different between Y-Elite and Pro dancers, although one of the COMT genotypes was different. Y-Elite dancers had higher trait anxiety scores than Pro dancers for these genotypes before competition (ps < 0.03), although no significant association was observed between both genotypes and scores on the STAI across conditions. Their moods were significantly different through the four conditions (p < 0.004). Pro dancers’ moods were also more stable than those of the Y-Elite dancers in the presence of pain. The results indicate that 5-HTTLPR and COMT play a crucial role in dancers’ anxiety and mood during pain (ps < 0.05). Pro dancers are probably predicted by their lower neuroticism and mood scores and their better adaptation to stress than Y-Elite dancers. The 5-HTTLPR and COMT genes may be influencing the sensitivity to the environment. Youth elite ballet dancers need to understand the relationship between pain and physical activity from an early stage.